Effect of wear on stress distributions and potential fracture in teeth - Ford, Christopher; Bush, M.; Lawn, B. (Srpinger US, 2009)
Finite element analysis is conducted on a tooth model with different degrees of wear. The model is taken as a hemispherical shell (enamel) on a compliant interior (dentin). Occlusal loading is simulated by contact with a flat or curved, hard or soft, indenter. Stress redistributions indicate that development of a wear facet may enhance some near-contact fracture modes (cone-ring cracks, radial-median cracks, edge-chipping), but have little effect on far-field modes (margin cracks). Contacts on worn surfaces with small, hard food objects are likely to be most deleterious, generating local stress concentrations and thereby accelerating the wear process. More typical contacts with larger-scale soft foods are unlikely to have such adverse effects. Implications concerning dietary habits of animals is an adjunct consideration in this work.